Development of an In vitro Propagation Protocol for Thalictrum foliolosum: An Endangered Medicinal Plant (Plant Tissue Culture and Biotechnology, 2023)
The present study has developed a reproducible in vitro micropropagation protocol for endemic and endangered Thalictrum foliolosum by using leaf and root segments. Thalictrum foliolosum possesses high medicinal properties due to the presence of valuable phenols, flavonoids and alkaloids. The plants are uprooted due to their high medicinal and clinical applications, hence can lead to extinction threat. In vitro leaf and root, explant was used for induction of multiple shoots on MS medium supplemented with plant growth regulators like benzyl amino purine(BAP), indole-3- butyric acid (IBA), 1-Naphthalene acetic acid (NAA) and indole-3-acetic acid (IAA) alone or in combination.  The best positive response for the formation of shoots from the leaf segment was obtained from MS media supplemented with BAP (1.0 mg/l) + NAA (0.6 mg/l) after 4 weeks and Maximum roots were formed on MS + IBA (0.6 mg/l) within 4-5 weeks. Likewise, the maximum percentage of shooting and rooting from root explant was obtained in MS + BAP (0.8 mg/l) + TDZ (0.4 mg/l) and MS + IAA (1.0 mg/l) + NAA (2.0 mg/l) after 4 weeks. The well-rooted acclimatized plantlets were successfully transferred to field conditions.Plant Tissue Cult. & Biotech. 33(1): 47-56, 2023 (June)